A Review Report on Important Approches of Floating Drug Delivery System - Katiyar, Prashant Kumar (Asian Journal of Pharmaceutics (AJP), 2017)
Floating drug delivery systems (FDDS) are controlled release drug delivery systems, which get retained in the stomach for longer periods, thus helping in absorption of drug for the intended duration of time. Gastricretentive drug delivery devices can be useful for the spatial and temporal delivery of many drugs. In general, drugs with narrow therapeutic window and prone to degradation in intestine and colon along with drugs having low retention time in gastrointestinal tract (GIT) are selected for FDDS which helps drugs to stay long time in stomach thus increasing gastric residence time and reduces dosing frequency. The present review article shows the various methods of FDDS for increasing retention time of drugs in GIT. Key words: Dosing frequency, floating drug delivery systems, gastric